The effectiveness of a training program to equip teachers with the skill of designing interactive instructional activities using the Smart Notebook and their attitudes towards it at the Governmental schools of the Directorate of Education in Tulkarm - Shaqour, Ali Zuhdi; Bdair, Maram Ahmad (Journal of Educational and Psychological Sciences, 2021)
This study aimed at investigating the effectiveness of a training program to equip female teachers with the skill of designing interactive instructional activities using Smart Notebook, in addition to their attitudes towards this application at the Governmental schools of the Directorate of Education in Tulkarm.The study sample consisted of 21female teachers of different major specializations in 2 basic schools in Tulkarm City during the second semester of the academic year (2018/2019). The training program was applied to them for a period of two weeks after applying the pre-test and then applying the study tools represented by the post-test and the interview. The study found a statistically significant difference at (α = 0.05) in the trainee teachers’ acquisition of the skills of designing interactive activities, using the Smart Notebook application that is due to the training program. The results also indicated that trainees were also satisfied with the procedure of implementing the program, and the various training conditions through a direct interview with a sample of trainees. Also, in light of the results of the study, the researchers recommended adopting the program in other schools, in addition to providing an original version of the application in these schools.